ISOLATION OF LECANORIC ACID AND USNIC ACID FROM LICHEN Umbilicaria calvescens Nyl. - Ramos Chávez, Judith (2018)
From the lichen Umbilicaria calvescens Nyl., was made the isolation of the major lichen compounds: usnic acid and lecanoric acid. Isolation of lichen compounds was performed by column chromatography (CC) and thin layer chromatography (CCF) of the extracts made in acetone and hexane. Yellow crystals were obtained from the n-hexane extract, while a white solid was obtained from the acetone extract. The crystals obtained were identified by their physical characteristics and by the UV, IR, MS, 1 H-NMR and 13C-NMR spectra.